Non-destructive and direct determination of the degree of substitution of carboxymethyl cellulose by HR-MAS 13C NMR spectroscopy. (1st August 2017) - Ferro, M.; Castiglione, F.; Panzeri, W.; Dispenza, R.; Santini, L.; Karlsson, H.J.; de Wit, P.P.; Mele, A.
Highlights: High resolution magic angle spinning (HR-MAS) 13 C NMR spectra allows the determination of DS in CMC samples. The HR-MAS NMR method is direct, non-destructive, and it does not require any sample pre-treatment. The DS determination can be done in purified, unpurified, high- and low-viscosity samples of any origin (wood or linters). HR-MAS NMR allows the effective DS determination of sample with low solubility containing high amount of unsubstitued cellulose Abstract: We report on the direct assessment of the degree of substitution (DS) of carboxymethyl cellulose (CMC) by High Resolution Magic Angle Spinning (HR-MAS) 13 C NMR spectroscopy. The method is applied to industrial CMCs with low and high viscosity and nominal DS, purified and technical samples, and from cellulose linters or wood. The preparation of a set of purified CMC working standards with accurate DS values for the method validation is also described. The DS values determined via HR-MAS 13 C NMR on the industrial samples are critically compared to the corresponding values achieved through the USP 37 〈281〉 method (ASH method) and the HPLC method, and the advantages and limitations of the HR-MAS NMR method highlighted. Finally, the HR-MAS NMR approach allowed the accurate DS assessment in CMC with low DS, characterized by a non-negligible fraction of non-functionalized cellulose. The proposed "effective DS" accounts for the DS of the solvent-exposed CMC.